ESRα Promoter Methylation May Modify the Association Between Lipid Metabolism and Type 2 Diabetes in Chinese Farmers - Zhou, Guoyu; Liu, Lihua; Li, Xing; Hou, Xiangbo; Wang, Ling; Sun, Renjie; Huang, Hui; Li, Zhiyuan; Li, Wenjie; Wang, Chongjian; Ba, Yue (Frontiers in Public Health, 2021)
Objective: This study is aimed to explore the potential association among the estrogen receptor alpha (ESRα) promoter methylation, lipid metabolism and the risk of type 2 diabetes mellitus (T2DM). Methods: A total of 1143 rural residents were recruited randomly from Henan Province, China. The circulating methylation levels in ESRα promoter region were determined by quantitative methylation-specific polymerase chain reaction. Serum high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), triglyceride (TG), total cholesterol (TC) and fasting plasma-glucose (FPG) were measured. Results: The ESRα promoter methylation levels were negatively associated with HDL-C levels whether gender stratification was performed (P < 0.05) and positively correlated with LDL-C in men (P < 0.05). Each unit standard deviation (SD) increment in TG was associated with a 43% increase (95% CI: 1.25, 1.64) in the risks of T2DM in all participants, a 36% increase (95% CI: 1.13, 1.64) in the risks of T2DM in men and a 49% increase (95% CI: 1.21, 1.83) in the risks of T2DM in women. Furthermore, each SD increment in HDL-C was associated with a reduction of 25% (OR = 0.75, 95% CI: 0.58, 0.97) in the risks of T2DM in men, and the risk of T2DM in men may be more susceptible to HDL-C than that in women (P for interaction < 0.05). Additionally, we found that the risk of T2DM in participants with lower methylation levels (≤4.07%) were more susceptible to HDL-C (P for interaction < 0.05). Conclusions: These findings suggested that lipid metabolism was associated with ESRα promoter methylation levels and the risk of T2DM. Besides, the levels of ESRα promoter methylation and gender can modify the association of HDL-C and T2DM.